Transport of a Sliding Wigner Crystal in the Four Flux Composite Fermion Regime - Chi Zhang; Rui-Rui Du; M.J. Manfra; L.N. Pfeiffer; K.W. West (Physical Review B, 2015)
In two-dimensional (2D) electron systems, Wigner crystals (WC) and fractional quantum Hall effect (FQHE) liquids are competing ground states under low temperatures (T) and high magnetic fields (B). Here we report differential conductivity results demonstrating the reentrant insulating phase around ν=1/5 in a 2D hole system in AlGaAs/GaAs quantum wells and unexpected features in the solid-liquid phase transition between WC and FQHE liquids in ultrahigh magnetic fields up to 45 T. Remarkably, the electric field (E) plays an equivalent role as the temperature does in our phase diagram. From the E−T “duality” analysis, a characteristic length of 450 nm is derived, which can be understood as the phase-coherent domain size of WC. Moreover, evidence shows that with weak disorder the insulating phase and composite fermion liquid could be coexisting around ν= 1/5, pointing to the possibility that the insulating phase is the four flux quantum Wigner crystal, as proposed by theories.